A Retrospective Study of Egg Production, Fertility and Hatchability of Farmed Ostriches in Botswana - Dzoma, B.M.; Motshegwa, K. (International Journal of Poultry Science, 2009)
A retrospective observational epidemiological study was conducted to study on-farm reproductive performance (egg production, fertility and hatchability) on 4 ostrich farms in Botswana. An average of 600 birds per farm and a total of 38,447 eggs were involved. The period of operation of the farms ranged from 2-11 years. Fertility ranged from 63.5-89% (μ = 76.3%), while, hatchability ranged from 39.4-83.6%(μ = 53.8%). Hatchability averaged 54.2 and 52.4% and on farms employing the male: female breeding ratio of 1: 2 and 1: 3, respectively, while, it averaged 62.9 and 65.9% on farms employing natural and artificial incubation, respectively. Egg production, fertility and hatchability were all competitive when compared to other country figures although there is still vast room for improvement. Record keeping needs to be encouraged on farms.